Logika Matematika : Sejarah, Pengertian, Aliran, Kegunaan - Prihaten Maskuliah; Firanti Nur Hayoto; Dewi Mawadda Rumaf (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2026)
This article explores mathematical logic as a fundamental discipline within mathematics that systematically investigates the principles of valid, coherent, and consistent reasoning. Mathematical logic serves as an essential foundation for developing structured thinking and constructing well-grounded, persuasive arguments supported by clear justification. It primarily focuses on the processes of reasoning, argumentation, and formal proof, enabling individuals to distinguish between valid and invalid conclusions. By establishing precise rules and logical structures, mathematical logic provides a rigorous framework for assessing the strength and consistency of arguments. The discipline emphasizes clarity, objectivity, and analytical accuracy in examining propositions and their relationships. In practice, mathematical logic is presented through the use of symbolic representations, formal logical statements, connectives, quantifiers, and truth tables to analyze patterns of reasoning and verify the truth values of statements. These systematic tools allow complex ideas to be evaluated methodically, prevent logical fallacies, and ensure that conclusions are derived from sound and demonstrable reasoning principles.